FAMILY MEALTIME AND ITS CORRELATION WITH DEPRESSIVE DISORDER - Saifi, Areeba Binte Junaid; Abrar, Amna; Dars, Jawed; Adhami, Zoha (Journal of Pakistan Psychiatric Society, 2022)
Introduction: Family mealtimes provide an opportunity for healthy interaction among the members of a family. A decrease in mental health disorders has been reported with the increasing frequency of family meals.Objective: Our cross-sectional study aimed to assess the frequency of the depressive disorder in medical students of Karachi and investigate its relationship with family mealtime frequency. This study will help raise awareness about the significance of family connectedness and its relation to depressive disorder.Design: This study analyzed 376 males and females. A self-administered proforma formulated from the literature review, and PHQ-9 scale was used to assess family dynamics and depressive disorder respectively.Place and Duration of Study: The study took place in Karachi from September 2019 to April 2020.Methodology: Proforma was circulated online using the snowball sampling technique. Students who were non-consenting, married, hostel residents, already diagnosed with depressive disorder, taking any psychotropic drugs, or witnessed any emotional trauma within the last one month were excluded. The data was evaluated using IBM SPSS Statistics v20.Results: Overall 93.9% of students showed depressive disorder of various severities. A significant relationship was found between family mealtime frequency and depressive disorder with a p-value of 0.025.Conclusion: Findings suggest that family mealtimes may have a positive influence on mental health disorders and can serve as a milieu for intrafamilial bonding, thus lowering the depressive scores and enhancing mental health.